Requirements for a successful defence reaction by the CRISPR–Cas subtype I-B system. (20th November 2013) - Stoll, Britta; Maier, Lisa-Katharina; Lange, Sita J.; Brendel, Jutta; Fischer, Susan; Backofen, Rolf; Marchfelder, Anita
Abstract : Uptake of foreign mobile genetic elements is often detrimental and can result in cell death. For protection against invasion, prokaryotes have developed several defence mechanisms, which take effect at all stages of infection; an example is the recently discovered CRISPR (clustered regularly interspaced short palindromic repeats)–Cas (CRISPR-associated) immune system. This defence system directly degrades invading genetic material and is present in almost all archaea and many bacteria. Current data indicate a large variety of mechanistic molecular approaches. Although almost all archaea carry this defence weapon, only a few archaeal systems have been fully characterized. In the present paper, we summarize the prerequisites for the detection and degradation of invaders in the halophilic archaeon Haloferax volcanii . H. volcanii encodes a subtype I-B CRISPR–Cas system and the defence can be triggered by a plasmid-based invader. Six different target-interference motifs are recognized by the Haloferax defence and a 9-nt non-contiguous seed sequence is essential. The repeat sequence has the potential to fold into a minimal stem–loop structure, which is conserved in haloarchaea and might be recognized by the Cas6 endoribonuclease during the processing of CRISPR loci into mature crRNA (CRISPR RNA). Individual crRNA species were present in very different concentrations according to an RNA-Seq analysis and many were unable to trigger a successful defence reaction. Recognition of the plasmid invader does not depend on its copy number, but instead results indicate a dependency on the type of origin present on the plasmid.